SP0021 The Association Between Fatigue, Sleep and Physcial Activity in Patients with Rheumatoid Arthritis. (9th June 2015) - Loeppenthin, K.
Abstract : Background: It is well establish that absence of fatigue and good sleep are important for maintaining good physical and mental health. However, evidence shows that fatigue and poor sleep are prevalent and severe problems for patients with rheumatoid arthritis. Physical activity may both represent a health promoting behavior in addition as a strategy for symptom management. Aim: The overall focus for the lecture will be on fatigue and sleep in addition to a health promotion and health prevention perspective of physical activity and in the context of fatigue and sleep. The specific focus areas will be on: 1) Physical activity in a health promotion perspective 2) The association between physical activity, fatigue and sleep in patients with rheumatoid arthritis 3) Perspectives of physical activity as a part of the management of symptoms related to rheumatoid arthritis Method: The lecture is primary based on results from a qualitative study (n=16) with the aim to investigate the patients' experience of physical activity maintenance, and a cross-sectional study (n=500), with the aim to examine the association between fatigue, sleep and physical activity in patients with rheumatoid arthritis. Results: The qualitative study show that patients with rheumatoid arthritis experience maintenance of physical activity as important for a sense of wellbeing and increased control over bodily function and symptoms. Furthermore, the cross-sectional study documented a high prevalence (61%) of poor sleep in patients with rheumatoid arthritis and that different dimensions of fatigue are of importance for the association to physical activity and sleep respectively. Perspective: The lecture will contribute with knowledge regarding the importance of symptom management for patients with rheumatoid arthritis, including the importance of implementing a health promotion perspective in clinical practice. Disclosure of Interest: None declared